A Study of Polymerase Chain Reaction in Cerebrospinal Fluid for Diagnosis of Tuberculous Meningitis - Sheena Gupta; Alpa Gupta; Sanober Wasim; Aarti Kotwal; Nowneet Kumar Bhat (National Journal of Community Medicine, 2016)
Introduction: Tuberculous Meningitis (TBM) is the commonest type of CNS tuberculosis encountered in children of India. This study was undertaken to evaluate the role of TB Polymerase Chain Reaction (PCR) in CSF for rapid diagnosis of TBM.